Clinical and cognitive assessment in Friedreich ataxia clinical trials: a review - Darriba, Álvaro; Munnich, Arnold; Cardoso-Leite, Pedro; Funalot, Benoît; Waszak, Florian (Frontiers in Neurology, 2025)
Friedreich ataxia (FRDA) is the most common type of inherited ataxia. It is a neurodegenerative disorder characterized by progressive gait and limb ataxia, dysarthria, areflexia, and reduced proprioception and vibration sensation. Although a number of clinical trials have been conducted, there is currently no cure for this disease. In this article we review those clinical trials with a focus on the instruments used as endpoints to assess clinical progression, and discuss the potential benefits of integrating additional measures, including assessments from overlooked domains. We also review tools used to evaluate cognitive functions in individuals with FRDA, particularly those employing quantitative, objective, and time-based measures. We argue for the inclusion of cognitive and speech-related assessments in clinical trials, and examine the potential of developments in cognitive neuroscience and technology to address current measurement challenges and support more accurate and comprehensive evaluation of treatment effects. These innovations have the potential to complement existing approaches, enhance trial design, and advance clinical care.